Evolvability under climate change: Bone development and shape plasticity are heritable and correspond with performance in Arctic charr (Salvelinus alpinus). Issue 4 (19th May 2021) - Campbell, Calum S.; Adams, Colin E.; Bean, Colin W.; Pilakouta, Natalie; Parsons, Kevin J.
Abstract: Environmental conditions can impact the development of phenotypes and in turn the performance of individuals. Climate change, therefore, provides a pressing need to extend our understanding of how temperature will influence phenotypic variation. To address this, we assessed the impact of increased temperatures on ecologically significant phenotypic traits in Arctic charr ( Salvelinus alpinus ). We raised Arctic charr at 5°C and 9°C to simulate a predicted climate change scenario and examined temperature‐induced variation in ossification, bone metabolism, skeletal morphology, and escape response. Fish reared at 9°C exhibited less cartilage and bone development at the same developmental stage, but also higher bone metabolism in localized regions. The higher temperature treatment also resulted in significant differences in craniofacial morphology, changes in the degree of variation, and fewer vertebrae. Both temperature regime and vertebral number affected escape response performance, with higher temperature leading to decreased latency. These findings demonstrate that climate change has the potential to impact development through multiple routes with the potential for plasticity and the release of cryptic genetic variation to have strong impacts on function through ecological performance and survival. Abstract : Bone development differs with temperature in Arctic charr. Here, bone development was measured from pixels in images of stained specimens with blue indicating the presence of cartilage, and red/purple indicating ossified bone. Development was also quantified from shape variation collected using the red points. Our findings indicated reduced levels of ossified bone in warmer temperature along with ecologically relevant shape changes. Research Highlights: Fish populations will face several challenges under climate change including alterations of phenotypic development. We found that temperature can alter the development of bone, including a decrease in the amount of ossification with increasing temperature, changes in shape, and vertebrate number. These responses are heritable and correspond to reductions in predator escape performance indicating they have a strong potential to influence evolution in a changing world.